Propagation of Apis cerana Fabr. (Hymenoptera: Apidae) prospective queen bee - Jasmi, Jasmi; Syarifuddin, Syarifuddin; Putra, Dewirman Prima (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Honey bee, Apis cerana Fabr. (Hymenoptera; Apidae) has been domesticated in West Sumatra. Various attempts to obtain practical and effective methods for multiplying superior colonies have been made. Optimizing the role of worker bees as a determinant of the future colony can be done by creating an emergency colony condition (queen bee not present). In this kind of colony, the worker bees immediately produced a new queen bee candidate from young larvae. This research was conducted at Trigona Mandiri Apiary, Padang Pariaman, West Sumatra, Indonesia from February to May 2019. The method used was a complete randomized design with four treatments and 10 replications. Results showed that the comb isolation technique was the best method for producing new queen bee candidates and increasing the appearance of young queen bee (gyn). The mean appearance of gyn from pupae was 4.8 per colony so that the number and quality of pupae to be maintained can be selected.